A study on assessment of depression and factors associated with it among medical students of Raichur Institute of Medical Sciences, Raichur - Kirte, Rahul C.; Fahim, M. A. (International Journal Of Community Medicine And Public Health, 2018)
Background: Depression among medical students represents a neglected public health problem in India. Early onset depression among medical students interferes with psychological, social, and academic functioning. Clearly, depression in medical students is of paramount importance and warrants serious study to detect early symptoms of depression. This study was conducted to find out the prevalence and the risk factors associated with depression among medical students of RIMS, Raichur. Methods: Cross-sectional study conducted among medical students from 1st year to final year of RIMS, Raichur who gave consent. Socio-demographic and risk factors details were collected using pre-tested, semi-structured questionnaire and beck depression inventory scale was used to assess the depression level. Data was analyzed using Epi-Info 7 software and appropriate statistical tests were applied. Level of significance was set at a p<0.05. Results: Of the 421 medical students participated in the study, 214 (50.83%) were males and 207 (49.17%) were females. The overall prevalence of depression was found to be 22.09%. Statistically significant association of depression was found with family history (χ2=4.23, p<0.05), family problems (χ2=61.98, p<0.001), relation with parents (χ2=51.82, p<0.001), high expectations from parents (χ2=22.76, p<0.001), those who regret joining MBBS (χ2=30.44, p<0.001), relationship status (χ2=4.63, p<0.05). Conclusions: Our findings emphasize the importance of screening for depression of medical students on a regular basis for early detection and appropriate intervention like group counseling, stress management training, support services etc. to protect this valuable future human resource.